Click‐chemistry of polymersomes on nanoporous polymeric surfaces. Issue 13 (6th March 2016) - Rein, Christian; Nissen, Steen; Grzelakowski, Mariusz; Meldal, Morten
ABSTRACT: A facile click chemistry method of immobilizing surface‐functionalized polymer vesicles on casted polymeric PAN substrates is described. Microporous PAN membranes were subjected to hydrochloric acid hydrolysis to obtain surface carboxylates. The carboxylic groups were activated with EDC/NHS‐solution and were then reacted with propargylamine to introduce alkyne groups for CuAAC reactions. The alkyne functionality of the modified membrane surface was verified by reaction with an azide functional click dye both before and after the immobilization of azide‐functionalized ABA vesicles. The efficient postfunctionalization of the membrane with alkyne allowed quantitative coverage of the membrane surface with a polymersome monolayer, as confirmed by immobilization of polymerzomes loaded with a fluorescent dye. Polymersome monolayers immobilized on alkyne functionalized PAN‐membranes were characterized by cryo‐SEM and monolayers were confirmed by atom force microscopy. These methods opens up new avenues for preparing membrane based filtration and sensor technologies. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2032–2039 Abstract : Self‐assembly of azide modified ABA polymersomes on nanoporous membranes was guided by CuAAC mediated click chemistry. Through charge–charge interactions the polymersomes organize on alkyne functionalized acrylonitrile membranes and are immobilized through triazole formation.